The defector - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2009)
Gabriel Allon's idyllic world is once again thrown into turmoil with shocking news from London. The defector and former Russian intelligence officer Grigori Bulganov, who saved Gabriel's life in Moscow, has vanished without a trace. British intelligence is sure he was a double agent all along, but Gabriel knows better. He also knows he made a promise--a promise that leads to a deadly duel of nerve and wits with one of the world's most ruthless men: the murderous Russian oligarch and arms dealer Ivan Kharkov.